2022
DOI: 10.3389/fvets.2022.1059054
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and antimicrobial resistance of staphylococci other than Staphylococcus aureus from domestic animals and livestock in Africa: a systematic review

Abstract: IntroductionStaphylococci other than Staphylococcus aureus (SOSA) in animals are becoming more pathogenic and antibiotic resistant and can potentially disseminate to humans. However, there is little synthesized information regarding SOSA from animals in Africa. This systematic review provides a comprehensive overview of the epidemiology and antimicrobial resistance of SOSA in companion animals (pets) and livestock in Africa.MethodThis systematic review (PROSPERO-CRD42021252303) was conducted according to the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…The detection of novel STs was not unexpected, especially considering the huge diversity found in the latter species, and the ecological niche investigated combined with the limited international dog trafficking in sub-Saharan Africa. The presence of Staphyloccoccaceae in African dogs was previously investigated, with a focus on clinical samples ( 21 ). Overall, two species, namely S. epidermidis and S. pseudintermedius , were predominantly reported in these studies even if M. lentus , S. haemolyticus, and S. cohnii were also identified on rare occasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of novel STs was not unexpected, especially considering the huge diversity found in the latter species, and the ecological niche investigated combined with the limited international dog trafficking in sub-Saharan Africa. The presence of Staphyloccoccaceae in African dogs was previously investigated, with a focus on clinical samples ( 21 ). Overall, two species, namely S. epidermidis and S. pseudintermedius , were predominantly reported in these studies even if M. lentus , S. haemolyticus, and S. cohnii were also identified on rare occasions.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the potential reservoirs in different regions of the world and the circulation of MDR Staphylococcaceae is definitively needed. While such information is progressively acquired especially in developed countries, there is a lack of information in other parts of the world including the African continent ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The whole genome sequencing on all isolates was performed on the NextSeq 2000 (Illumina) utilizing the P2 (300) cycle kit reagents (Illumina,San Diego, CA). Whole genome sequence analysis was performed as described by Ocloo et al, 2022 (22)…”
Section: Dna Extraction and Whole Genome Sequencingmentioning
confidence: 99%
“…Little is known about the prevalence and epidemiology of staphylococcus other than S. aureus (SOSA),especially in Africa (4), and only a few cases of SOSA transmission between humans and animals have been reported globally (12,13). A recent systematic review showed that most research on SOSA in animals is focused on cattle (11). However, pigs are one of the most common livestock globally and in South Africa (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…SOSA in animals is becoming more pathogenic increases antibiotic resistant and can potentially disseminate to humans [ 18 ]. In the U.S., mortality caused by MRSA remains the highest for any antibiotic-resistant pathogen, reported by the CDC to be at ~20,000 in 2018.…”
Section: Introductionmentioning
confidence: 99%